Probability applications in mechanical design - Fisher, Franklin E., 1933- (Mechanical engineering (Marcel Dekker, Inc.), 2000)
This text seeks to clarify mechanical fatigue and design problems by applying probability and computer analysis, and further extending the uses of probability to determine mechanical reliability and achieve optimization. It solves examples using commercially available software.